What to call ourselves? representation and terminology of mixed heritage Japanese-Filipinos - Hara Megumi (2012)
Mixed heritage population has been represented in different ways from other "ordinary" people of the society. The representation of ethnicity/race reveals how people view ethnicity/race and culture based on the power structure of a society. This paper discusses the representation and terminology of Japanese-Filipinos who were born to Japanese and Filipino parents through the description analysis of books, newspapers and radio transcriptions. It also examines what the Japanese-Filipinos want to be called and what they call themselves by in-depth interviews including chat interviews with Japanese-Filipino youth. The development process of terms reflects the sensational attitude of media and social movement of NGOs in both countries in last two decades. More recently, the groups of Japanese-Filipinos have been formed in different places and renaming themselves. This movement of Japanese- Filipinos mirrors their seeking of identity and social acceptance from the societies. The paper claims that terms have been changed due to the negative representation that has been implicated throughout the years regardless of the first intention, yet it is a necessary process for their flexible identity depends on the circumstances.
Keywords: Filipino Japanese